Pengaruh Kepuasan Kerja terhadap Kinerja Staff di Departemen Food Preparation di Hotel Borobudur Jakarta - anisa fadilla, septya; Ferdian , Feri (Jurnal Ragam Pengabdian, 2026)
This study investigates the effect of job satisfaction on staff performance in the Food Preparation Department of Hotel Borobudur Jakarta. Using a quantitative associative-causal design, data were collected through Likert-scale questionnaires from 105 employees selected by simple random sampling. The data were analyzed using descriptive statistics, classical assumption tests, and simple linear regression with IBM SPSS Statistics 26. The instruments were valid (r-count > 0.361) and reliable, with Cronbach's Alpha values of 0.922 for job satisfaction and 0.959 for performance. Descriptive analysis showed that both job satisfaction (mean = 3.47) and staff performance (mean = 3.46) were categorized as good. Regression analysis produced the equation Y = 4.625 + 0.862X, with a t-value of 13.712 (Sig. = 0.000), indicating that job satisfaction has a positive and significant effect on staff performance. The coefficient of determination (R² = 0.646) indicates that job satisfaction explains 64.6% of the variance in staff performance. These findings highlight the importance of fair compensation, transparent promotion, and supervisory support to improve employee performance.